2016
DOI: 10.1016/j.joa.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Atrial arrhythmias in inherited arrhythmogenic disorders

Abstract: Atrial arrhythmias are being increasingly recognized in inherited arrhythmogenic disorders particularly in patients with Brugada syndrome and short QT syndrome. Atrial arrhythmias in inherited arrhythmogenic disorders have significant epidemiologic, clinical, and prognostic implications. There has been progress in the understanding of underlying genetic characteristics and the mechanistic link between atrial arrhythmias and inherited arrhythmogenic disorders. Appropriate management of these patients is of para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 82 publications
(135 reference statements)
0
8
0
Order By: Relevance
“…A clinical study involving 46 BrS patients (39 male and 7 female) showed that 5 (3 male and 2 female) exhibited supraventricular tachycardias (Liu et al, 2015). Another clinical study (Hasdemir, 2016) emphasized the prevalence of atrial arrhythmias in BrS patients. In fact, mutations in the SCN5A gene have been found responsible for atrial fibrillation, Long QT syndrome type 3, sick sinus syndrome type 2, idiopathic ventricular fibrillation, and heart block type 1A (Olson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study involving 46 BrS patients (39 male and 7 female) showed that 5 (3 male and 2 female) exhibited supraventricular tachycardias (Liu et al, 2015). Another clinical study (Hasdemir, 2016) emphasized the prevalence of atrial arrhythmias in BrS patients. In fact, mutations in the SCN5A gene have been found responsible for atrial fibrillation, Long QT syndrome type 3, sick sinus syndrome type 2, idiopathic ventricular fibrillation, and heart block type 1A (Olson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants impairing I Na channel function along with structural remodeling promote AVNRT by prolonging refractoriness and slowing conduction velocity. Reduced levels of I Na are known to depress I Na ‐dependent parameters such as excitability and conduction, leading to heterogeneous prolongation of refractoriness, thus facilitating development of unidirectional block and reentry, giving rise to AVNRT 2,5 …”
Section: Discussionmentioning
confidence: 99%
“…Atrioventricular nodal reentrant tachycardia (AVNRT) is the most common form of paroxysmal supraventricular tachycardia (PSVT), and most forms of AVNRT are created by reentry between two (or more) atrial connections to the atrioventricular (AV) node 1 . Atrial vulnerability and atrial electrical/structural remodeling that leads to reentrant circuits in AVNRT are largely unknown 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial fibrillation can be the first clinical presentation of the SQTS, particularly in patients diagnosed with lone AF ( Hasdemir, 2016 ). Furthermore, the incidence of AF has been reported to be higher in patients with SQT2 than other forms of SQTS (63% vs. 21%, p = 0.012 ( Harrell et al, 2015 )).…”
Section: Introductionmentioning
confidence: 99%